2008
DOI: 10.1007/s12026-008-8027-z
|View full text |Cite
|
Sign up to set email alerts
|

Intrinsic and extrinsic control of effector T cell survival and memory T cell development

Abstract: Following infection or vaccination T cells expand exponentially and differentiate into effector T cells in order to control infection and coordinate the multiple effector arms of the immune system. Soon after this expansion, the majority of antigen-specific T cells die to reattain homeostasis and a small pool of memory T cells forms to provide long-term immunity to subsequent re-infection. Our understanding of how this process is controlled has improved considerably over the recent years, but many questions re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
43
0

Year Published

2010
2010
2014
2014

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 43 publications
(45 citation statements)
references
References 159 publications
(209 reference statements)
2
43
0
Order By: Relevance
“…Conventional CD8 þ T-cell responses rapidly contract after the peak of the response has been reached, and levels of CD8 þ T cells that remain after contraction are generally around 5% of peak levels. 41,42 In all our previous studies, immune responses induced by DNA tattoo showed similar kinetics, with contraction being close to complete about 1 week after the peak of the response. 16,38 In contrast, upon tattooing TTFC-E7-encoding DNA vaccines, we consistently observed that contraction of the induced CD8 þ T-cell response was delayed for about 3 weeks, and that the remaining frequencies after 4 weeks were still around 20% of the initial peak height (Fig.…”
Section: Discussionsupporting
confidence: 58%
“…Conventional CD8 þ T-cell responses rapidly contract after the peak of the response has been reached, and levels of CD8 þ T cells that remain after contraction are generally around 5% of peak levels. 41,42 In all our previous studies, immune responses induced by DNA tattoo showed similar kinetics, with contraction being close to complete about 1 week after the peak of the response. 16,38 In contrast, upon tattooing TTFC-E7-encoding DNA vaccines, we consistently observed that contraction of the induced CD8 þ T-cell response was delayed for about 3 weeks, and that the remaining frequencies after 4 weeks were still around 20% of the initial peak height (Fig.…”
Section: Discussionsupporting
confidence: 58%
“…The gating strategy of CD25 versus CD127 allowed the identification of regulatory T-cells (CD251CD127low) and the separation of cell populations that express CD127 at very high or low levels, respectively. In this panel, regulatory T-cell activation was assessed by anti-HLA-DR staining and the CD4 T-cell activation was estimated based on CD25 surface marker expression (14,26,28,29). Additionally, regulatory T-cells can be further divided in na€ ıve and memory regulatory T-cells and were calculated by CD31CD41 AND CD251CD127low AND CD45RO (high/low) (14).…”
Section: Panel Design and Gating Strategymentioning
confidence: 99%
“…The exact biochemical mechanism governing the survival of memory cells and apoptosis of the majority of effector cells is not well understood (1). As naïve T cells differentiate into effector and memory T cells, cytokines play a key role in their differentiation and survival.…”
mentioning
confidence: 99%